PENGARUH VISIBILITAS SOSIAL MEDIA TERHADAP KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN INDIVIDU PADA SAHAM SYARIAH - Shibghatalloh, Ahmad Hafiyyan; WAHYUDI, SUGENG (Maqdis: Jurnal Kajian Ekonomi Islam, 2024)
This study aims to examine the effect of Instagram users response to corporate Instagram post (likes and comments) toward individual ownership and institutional ownership of sharia stocks in Indonesia. The data collection method used is purposive sampling technique. The number of samples in this study were 258 companies registered in ISSI (Indonesia Sharia Stock Index) and having an active Instagram account. Data processing using SPSS.26 with Ordinary Least Square (OLS). The results showed that Instagram user respond increasing the institutional investor and individual investor in sharia stock. The interpretation for this findings that such Instagram activities increase the visibility of the company across a more diverse group of investors. This increase visibility makes information more accessible to individual and institutional investors, so that they are attracted to invest more in sharia stock. Sharia issuer companies should also use social media to provide valid information to potential investors. So that it can be one of the foundations of investors in choosing Islamic stocks. This research is the first study that used social media to measure Sharia Stock Ownership